1999
DOI: 10.1149/1.1391809
|View full text |Cite
|
Sign up to set email alerts
|

Effective Improvement on Barrier Capability of Chemical Vapor Deposited WSi x Using  N 2 Plasma Treatment

Abstract: This work studies the thermal stability of Cu/WSi x /p ϩ-n and Cu/WSiN/WSi x /p ϩ-n diodes in which the WSi x barrier layers were deposited by chemical vapor deposition to a thickness of about 50 nm using SiH 4 /WF 6 chemistry with the SiH 4 /WF 6 flow rates of 6/2 sccm, while the WSiN layers were formed by in situ N 2 plasma treatment on the chemically vapor deposited WSi x (CVD-WSi x) surfaces. Without N 2 plasma treatment, the thermal stability of Cu/WSi x (50 nm)/p ϩ-n junction diodes was found to reach 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This suggests that either the W–Si–N diffusion barrier between Cu and Si failed at this temperature or some of the Cu were consumed, diffused through W–Si–N layer, and reacted with underlying Si substrate, forming a highly resistive Cu silicide. It was reported that the failure temperatures of diffusion barriers against Cu, determined by XRD analysis (onset temperature of copper silicide formation), were 700 °C for the sputtered-deposited 10 nm thick W–Si–N film and 650 °C for chemical-vapor-deposited 50 nm thick W–Si–N film . If the thickness of the diffusion barrier is taken into account, it is strongly considered that the performance of ALD-grown W–Si–N is comparable to that of the sputter-deposited film and much better than that of the CVD one.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that either the W–Si–N diffusion barrier between Cu and Si failed at this temperature or some of the Cu were consumed, diffused through W–Si–N layer, and reacted with underlying Si substrate, forming a highly resistive Cu silicide. It was reported that the failure temperatures of diffusion barriers against Cu, determined by XRD analysis (onset temperature of copper silicide formation), were 700 °C for the sputtered-deposited 10 nm thick W–Si–N film and 650 °C for chemical-vapor-deposited 50 nm thick W–Si–N film . If the thickness of the diffusion barrier is taken into account, it is strongly considered that the performance of ALD-grown W–Si–N is comparable to that of the sputter-deposited film and much better than that of the CVD one.…”
Section: Resultsmentioning
confidence: 99%
“…(1) polycrystalline and amorphous Me-N, Me-C, Me-O and Me-B compounds, such as TiN x [25], VN x [26], ZrN x [27], NbN x [28], MoN x [21], HfN x [29], WN x [30], TaN x [31], WC x [32], TaC x [33], MoO x [34], TaO x [35] and TiB 2 [36], (2) polycrystalline and amorphous Me-Si compounds, such as MoSi x [37], WSi x [38] and TaSi x [39], (3) polycrystalline and amorphous Me alloys, such as TiW x [40], TaCo x and TaFe x [41], TaW x [42], NiNb x [43] and CuZr x [44].…”
Section: Metal-based Barriers As Liners For Cu Seed Depositionmentioning
confidence: 99%
“…Films of tungsten silicide (WSi x ) and related materials prepared by low pressure chemical vapor deposition (LPCVD) from WF 6 and reducing agents such as SiH 4 , Si 2 H 6 , and SiH 2 Cl 2 are widely used as interconnects and gate electrodes in most of electric devices (Chow et al 1983, Saraswat et al 1983, Wang et al 1999, Sell et al 2003. The WF 6 /SiH 4 gas system can be used to produce WSi x films at relatively low temperatures compared with the WF 6 /SiH 2 Cl 2 system.…”
Section: Introductionmentioning
confidence: 99%